Violência e literatura: a favela de Paulo Lins - Silva, Denise Helena (2016)
This dissertation proposes to analyze the novel “Cidade de Deus”, from Paulo Lins, published in 2002. It aims verify the relation between reality and ficcion in the novel and the way it gives the real representation in the narrative, particulary with regard to violence besides demonstrating the organization of geographicals that is present trough documentary and memoir writers marks. The dissertation seeks to answer the follow problematic: to what extent the image of reality, created by Paulo Lins, circumscribe in g urban violence and neo-realism? How Lins proposes a symbolic pace and memoirist to create, in "Cidade de Deus", a geographical and fictional space? "Cidade de Deus" brings aspects of brazilian reality, combined with ethnographic research on violence, crime and drug trafficking housing of "Cidade de Deus". The violent and brutal scenes give the novel the effect of reality and tries to awaken a reflection on violence and how it becomes a constitutive element in our country. The theoretical framework focuses on scholars as: Antonie Compagnon, Luiz Costa Lima, Karl Erik Schollhamer, Tânia Pellegrini, Alejandro Reyes, and Paulo Roberto Patrocínio. Among the final comments, it is demonstrated that, trough the representation of violence and its internal look, the author constructed a narrative based on crime, producing multiple meanings to the violence